Jews and Science (Purdue University Press, 2022)
Jews and Science examines the complicated relationship between Jewish identities and the evolving meanings of science throughout the history of Western academic culture. Jews have been not only the agents for study of things Jewish, but also the subject of examination by "scientists" across a range of disciplines, from biology and bioethics to anthropology and genetics. Even the most recent iteration of Jewish studies as an academic discipline-Israel studies-stresses the global cultural, economic, and social impact of Israeli science and medicine. The 2022 volume of the Casden Institute's Jewish Role in American Life series tackles a range of issues that have evolved with the rise of Jewish studies, throughout its evolution from interdisciplinary to transdisciplinary, and now finally as a discipline itself with its own degrees and departments in universities across the world. This book gathers contributions by scholars from various disciplines to discuss the complexity in defining "science" across multiple fields within Jewish studies. The scholars examine the role of the self-defined "Jewish" scholar, discerning if their identification with the object of study (whether that study be economics, criminology, medicine, or another field entirely) changes their perception or status as scientists. They interrogate whether the myriad ways to study Jews and their relationship to science-including the role of Jews in science and scientific training, the science of the Jews (however defined), and Jews as objects of scientific study-alter our understanding of science itself. The contributors of Jews and Science take on the challenge to confront these central problems.